Factors influencing consumers' trust in online purchase via social networking sites - Wan Mohamad Nazarie, Wan Nur Fazni (2012)
Internet is a mass medium that can be accessed anywhere. The Internet is integrated into nearly all aspects of activities including businesses. The advancement of Internet contributes to the development of electronic commerce (e-commerce) to conduct online business, and consumer trust plays an essential role in the development of e-commerce. However, lately, the trend of e-commerce has been shifted to a brand new platform that is called Social Networking Sites (SNSs). As in e-commerce, consumer trust is also important in SNSs. Therefore, the factors that influence consumer trust in online purchase using SNSs has become the primary concern of this research, since there are limited studies investigating the factors as compared to in e-commerce. In this study, four factors were examined which are propensity to trust, experience in Internet usage, testimonial, and monetary risk. The sample of this research consists of 129 respondents that have a Facebook account. Questionnaires were distributed through email and also posted on the researcher’s Facebook. Independent t-test, ANOVA and multiple regression analysis were used to test the relationships between variables used. The study revealed that propensity to trust and testimonial are the factors that influence consumers’ trust in online purchase via SNSs.